Implementing the Market Approach to Enterprise Support : An Evaluation of Ten Matching Grant Schemes - Phillips, David A. (World Bank, Washington, DC, 2014)
Developing viable new business is critical to recovery, and long-term growth, especially in transition economies. There has been a long history of public support of enterprise development, starting with centralized state agency initiatives, but moving more recently to decentralized instruments for development of the business services market. The window of time during which the benefits of intervention are likely to be greatest: when a market is in its infancy, and its development is constrained by uncertainty, and lack of information. Interventions for enterprise support should be demand-responsive, and flexibly organized. In some circumstances, centralized assistance may still be effective, but it is generally better to use competitive private service providers responding to enterprises' changing needs. The main task is to stimulate the private services sector, improving its capacity to respond to the demands of new, and expanding private enterprises. Support for enterprises has tended to be either free, or heavily subsidized. But such subsidies can be justified only if interventions efficiently supply goods. Providing technical, and management know-how can be a public good if it generates externalities - if, for example, know-how benefits can be disseminated at proportionately low additional cost. Any subsidy for an intervention should be temporary, and should be phased out when the main objective of intervention is achieved - that is, when the market takes off. Grants should generally be for know-how, not for equipment. There may be a case for unbundling the know-how component of loans (including feasibility studies, and follow-up expert services) for grant funding. A package combining loans and grants - through a single financial institution, or through separate institutions - may work provided safeguards can be put in place to prevent perverse use of grants. The matching grant model, which is used increasingly in the World Bank, and elsewhere, is one solution - but it must be justified, and carefully designed. After evaluating ten matching grant funds, the author concludes that performance is mixed. Best practice models are needed. Ensuring economic benefits requires proactive management, with clear objectives of market facilitation ("making a market"). And it requires a balance between rapid grant approval procedures, and careful selection of services for grants.